Associations of social determinants of health on likelihood of systemic hormone therapy use in midlife women - Juliana M. Kling; Anna E. Abraham; Ekta Kapoor; Kristin Cole; Mariam Saadedine; Chrisandra Shufelt; Stacey J. Winham; Stephanie S. Faubion (Biology of Sex Differences)
Abstract Objective Social determinants of health (SDOH) can have a significant impact on women’s health and quality of life. Little is known about the impact of SDOH during menopause, and whether certain SDOH impact the likelihood of using systemic hormone therapy (HT). Our objective was to evaluate the impact of SDOH on the likelihood of HT utilization among midlife women. Design Midlife women between the ages of 45–60 years were surveyed about their menopause experience between March and June of 2021. The questionnaire included information on medications used to treat menopause symptoms. From the electronic medical record demographic information and self-reported SDOH data were obtained, including the amount of exercise/physical activity, whether the participants felt stressed, social interactions, abuse in the last year, ability to pay for basics, diet, alcohol intake, smoking status, and whether participants had regular dentist visits. SDOH were compared between using/not using HT currently. Results One thousand nine hundred and eighty-eight women aged 45–60 years who received primary care at one of four geographic Mayo Clinic sites completed the survey and filled out SDOH questions within 2 years. Women were 54.4 years of age on average (SD 4.2), with a mean BMI of 30.2 (SD 7.5), and a majority White (97%). 258 (13.0%) women were currently using HT. In univariate analysis, women were less likely to be using HT if they had higher BMI (per 1 kg/m2 increase, OR = 0.97, 95% 0.95–0.99, p = 0.002) were unpartnered (OR = 0.66, 95% CI 0.45–0.99, p = 0.04) had lower education (compared to post graduate studies, high school graduate/GED or less: OR = 0.45, 95% CI 0.24–0.85, p = 0.01; some college/2 year degree: OR = 0.69, 95% CI 0.49–0.96,p = 0.03), or were a smoker (compared to those who never smoked, current smoker: OR = 0.38, 95% CI 0.18–0.83, p = 0.02; former smoker: OR = 0.71, 95% CI 0.52–0.96, p = 0.03). Women who used extra virgin olive oil as main fat in diet were more likely to be using HT (OR = 1.46, 95% CI 1.10–1.94, p = 0.009). No other SDOH were associated with HT. Conclusion Certain SDOH were associated with HT use for menopause treatment. Favorable SDOH likely correlate with better access to menopause care. To assure equitable menopause treatment for all women, clinicians should evaluate and address SDOH with their midlife women patients.